Evacuation Decisions during the Great East Japan Earthquake - Jan Dirk Schmöcker; Jun Ji; Fajar Prawira Belgiawan; Nobuhiro Uno (Findings)
We analyse evacuation decisions with data from a survey among 10,384 survivers of the 2011 Great East Japan earthquake. The decisions of individuals and families to evacuate or stay are influenced by the Tsunami warning system as well as the behaviour of the surrounding population which is modelled as the percentage of persons evacuating from a city. We formulate binary choice models with "field effects" where we try to control for the endogeneity with a 2-stage model approach. Our results quantify the field effect and suggest that with each minute the Tsunami warning arrives later, on average 3% less of the population are evacuating and surviving. We also show the importance of other variables, in particular the preparedness measures such as signage and evacuation drills.